2022
DOI: 10.1002/oby.23450
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic adaptation after combined resistance and aerobic exercise training in older women

Abstract: Objective: This study investigated whether combined aerobic and resistance training in older women leads to metabolic adaptation.Methods: A total of 80 women (64 White individuals; BMI: 30.0 [4.4] kg/m 2 ; age: 64.8 [3.5] years) followed 32 weeks of aerobic and resistance training. Body weight/ composition (dual-energy X-ray absorptiometry) and resting metabolic rate (RMR; indirect calorimetry) were measured at baseline, week 16, and week 32. Metabolic adaptation was defined as significantly lower measured ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Resistance exercise was an effective intervention for improving body composition by reducing body fat in middle-aged women with obesity [16,17]. However, the results of the present study showed no significant differences in body weight, BFP, or BMI among the groups.…”
Section: Discussioncontrasting
confidence: 77%
“…Resistance exercise was an effective intervention for improving body composition by reducing body fat in middle-aged women with obesity [16,17]. However, the results of the present study showed no significant differences in body weight, BFP, or BMI among the groups.…”
Section: Discussioncontrasting
confidence: 77%
“…Studies focused on older adults have demonstrated that aerobic combined with resistance training plans can increase metabolic rate and improve body composition. However, long-term training in older women can lead to metabolic adaptation and a decrease in metabolic rate 41 . This suggests that the optimal intensity for weight loss may vary due to individual differences, such as age.…”
Section: Discussionmentioning
confidence: 99%
“…Such phenomenon has been attributed to hormonal adaptations to the energy restricted-weight loss, of which the main features are elevated appetite, desire to eat, and reduced energy expenditure and satiety in response to food ingestion [30]. Importantly, a recent study conducted on 80 older women with obesity demonstrated that resistance and aerobic exercise without calorie restriction-induced weight loss resulted in a metabolic adaptation to the mild energy deficit induced by the intervention [31]. In another study, Rejeski et al [32 ▪▪ ] assessed changes in ghrelin and GLP-1 (orexigenic and anorexigenic, respectively) in 177 older adults with obesity and cardiometabolic diseases randomly assigned to weight loss alone, or weight loss plus aerobic or resistance exercise to evaluate the hormonal adaptations to weight loss.…”
Section: Weight Regainmentioning
confidence: 99%